Peningkatan hasil belajar matematika melalui model pembelajaran Problem Based Learning berbantuan media konkret siswa kelas 1 SDN Sawah Besar 01 - Himmatul Ulya; Mira Azizah; Ladung Antoko; Fine Reffiane (Pascasarjana Universitas PGRI Semarang, 2025)
This research aims to determine the improvement in learning outcomes of students in mathematics subjects measuring the length of objects using the Problem Based Learning (PBL) learning model assisted by concrete media for class I A students at SDN Sawah Besar 01 Semarang. This research is a type of classroom action research with research implementation consisting of pre-cycle, cycle I and cycle II. The data analysis technique in this research is descriptive quantitative. The subjects of this research were 28 students in class I A at SDN Sawah Besar 01 Semarang. Data collection uses learning outcomes and documentation. The collected data is analyzed by calculating the average score achieved by students. The results showed that in cycle I, the average results increased. This is evidenced by an increase from pre-cycle of 62.85, cycle I of 76.78 and in cycle II there was an increase of 87.14. So it can be concluded that the results of learning mathematics on addition and subtraction material using the Problem Based Learning (PBL) learning model (PBL) assisted by gestic media have increased and the results are satisfactory.